Testing, Testing, Read All About It: Canadian Press Coverage of the PISA Results - Stack, Michelle (Canadian Journal of Education/Revue canadienne de l’éducation, 2006)
This article is a critical discourse analysis of coverage in the National Post and the Globe and Mail concerning the Organisation for Economic Co‐operation and Development’s 2000 Programme for International Student Assessment (PISA). In this article, I have shown how numbers are interpreted through statistics to create a reality and analyzed the mechanisms used, through which information is constructed and reconstructed by and for the media. I have also explored how diverse voices are represented. The discourses of neoliberalism were embedded in the coverage of the PISA results and discourses that accentuated regional stereotypes were in use. Key words: policy, media education, neoliberalism L’analyse du discours critique présentée dans cet article porte sur la couverture dont a fait l’objet le Programme international pour le suivi des acquis des élèves (PISA) 2002 de l’Organisation de coopération et de développement économiques dans le National Post et le Globe and Mail L’auteure étudie comment les chiffres sont interprétés à travers des statistiques en vue de créer une réalité et quels sont les mécanismes utilisés pour construire et reconstruire l’information par et pour les médias. Elle explore en outre comment les diverses voix sont représentées. Les discours du néolibéralisme faisaient partie intégrante de la couverture des résultats du PISA ; des discours accentuant les stéréotypes régionaux y étaient utilisés. Mots clés : politiques, médias éducation, néolibéralisme